One Decade of Power Sector Privatization Programme in Nigeria: Issues and Challenges - Manjo, Yusuf Garba (Kashere Journal of Politics and International Relations, 2024)
Since Nigeria’s independence in 1960, the inadequacy of electricity institutions had resulted into incessant power outages, which prompted government to start the power sector reform in 2005 and concluded the exercise in 2013 with the privatization of the power institutions. The privatization was aimed at reducing inefficiency, mal-administration and government interference, increase generation and power supplies, and increase capital in to the sector. The scheme was based on the assumption that free market and competition would bring about efficiency and injection of private capital that would result in better performance and increased power supplies to enhance industrialization and development of the country. However, post-privatization electricity supplies showed little or no improvement, because the challenges confronting the sector are far from being resolved since 2013 till date. The methodology adopted for this research is descriptive analysis of content of information, mainly gathered from the secondary sources particularly in newspaper, journals, textbooks and archival documents. The study found that the challenges confronting the power sector after the privatization scheme include the inadequacy of gas for powering turbines, cost recovery and transmission challenges among others. The study concluded that privatization is yet to achieve its targets in the power sector-a decade after the exercise commenced.